FAMILY NYCTERIBIIDAE - Graciolli, Gustavo; Dick, Carl W.; Guerrero, Ricardo (Zootaxa, 2016)
This catalog presents eight species distributed among two genera and one subfamily of nycteribiid bat flies recorded in Colombia. For each genus we present synonymies and type species, and for each species account we present synonymies, disposition of type material, and specific localities and departments.